STUDI DESKRIPTIF TENTANG PERILAKU OPTAS (PASIF) SISWA DALAM PROSES PEMBELAJARAN DI KELAS VIIIB MTs JAMILURRAHMAN YOGYAKARTA - Rivaldy, Muhammad; Raharja, Alfath Akhmanuddin Rabbani; Thera, Muhammad Irsyad Van; Akbar, Panca Mega; Hamdi, Muadzin; Agustiar, Agustiar (Jurnal Manajemen Pendidikan, 2025)
This study aims to provide an in-depth description of the optas (passive) behavior of students during the learning process in class VIIIB of MTs Jamilurrahman Yogyakarta. The phenomenon of students who tend to remain silent, avoid asking questions, and show little participation is one of the common challenges teachers face in creating an effective and interactive classroom environment. This research employed a qualitative descriptive method with primary data sources consisting of students and teachers from class VIIIB. Data were collected through open-ended interviews comprising six questions for students and five questions for teachers. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that most students feel bored, shy, lack self-confidence, and are afraid of making mistakes during classroom activities. These emotional barriers lead them to remain silent and avoid expressing their opinions. From the teacher’s perspective, the students’ level of participation remains low due to both internal factors such as low motivation and self-confidence, and external factors such as limited two-way interaction between teacher and students.